Penambahan Genjer (Limnocharis flava) pada Pembuatan Garam Rumput Laut Hijau untuk Penderita Hipertensi: Yellow Velvetleaf (Limnocharis flava) Fortification in Ulva lactuca Seaweed Salt Production for Hypertensive Patients - Nurjanah - Nurjanah; Agoes Mardiono Jacoeb; Ramlan; Asadatun Abdullah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2020)
Ulva lactuca can be utilized as a raw material for seaweed salt production. The seaweed salt with low sodium and high potassium could be used as an alternative to regular table salt for hypertensive patient. This research was aimed to determine the amount/ratio of the addition of L. flava in production of seaweed salt according to dietary salt standards for hypertensive patients. The analyzed parameters were mineral composition, NaCl content, heavy metal content, and antioxidant activity of salt U. lactuca seaweed and addition of L. flava. The production of seaweed salt started with mixing the seaweed flour with water (1:10), heated in water bath shaker at 40 ºC for 10 min, and then subsequently dried at 60 ºC for 30 h. The U. lactuca extract had IC50 48.64 ppm (DPPH) and antioxidant capacity 246.92 (CUPRAC). The L. flava extract had IC50 138.86 ppm, and antioxidant capacity 116.92 µmol/g. The U. lactuca salt resulted in a yield 32.36%, ratio of Na:K 1.49, NaCl 23.90%, antioxidant activity 93.24 ppm (DPPH), and antioxidant capacity 129.15 µmol/g (CUPRAC). The U. lactuca:L. flava (1:1) salt resulted in a yield 22.78% , a ratio of Na:K 0.59, NaCl 21.05% , antioxidant activity 118.87 ppm (DPPH), and antioxidant capacity 104.07 µmol/g (CUPRAC). The addition of L. flava reduced the Na:K ratio to 0.59 as well as the NaCl levels with relatively small decrease in antioxidant activity and capacity.